UPAYA SUVERVISI AKADEMIK UNTUK MENINGKATKAN KEMAMPUAN GURU MADRASAH DALAM MEMBUAT RPP DI MADRASAH IBTIDAIYAH NEGERI 18 PIDIE - Nurhayati, Nurhayati (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2021)
Multimedia-based learning has great potential in changing the way students learn, obtain information, and adapt the information. Through multimedia-based learning, the ability of teacher learning techniques can be used optimally. In-class multimedia-based learning. This study aims to determine what can be influenced by multimedia-based learning. The factors that influence it are student learning motivation and student learning outcomes. The research will be conducted using qualitative research using observational research methods and interviews. The population in this study was 10  teachers at  Madrasah  Ibtidaiyah  Negeri  37  Pidie.  Sampling using probability sampling techniques with simple random sampling and obtained a sample of 10 people. The research data were obtained with guidance and training. The results showed that there was a significant effect of multimedia-based learning on student learning motivation. There is a significant effect of multimedia-based learning on student learning outcomes at Madrasah Ibtidaiyah Negeri 37 Pidie. So the teacher should be able to improve and use multimedia-based learning appropriately in accordance with the learning material so that learning is meaningful, effective, and efficient. Thus it can increase learning motivation and make it easier for students to understand the material so that students will get satisfying learning results.